Wandering myth: the figure of the Jew in the Franco cinema - Rúa Fernández, Carolina; Rúa Fernández, José Manuel (Historia y Comunicación Social, 2018)
Ilming was one of the most popular and effective Nazism’s tools for spreading racial hatred against Jews. Franco’s Spain, so close during the years of the Spanish civil war on Hitler’s Germany, tried to play the card of neutrality before the imminent Allied victory. However, even without a significant Jewish presence on the peninsula since the fifteenth century and away from Nazi anti- Semitism to adapt to the new international context, the official discourse is riddled with numerous allusions to Judeo-Masonic cahoots. The story of this obsession and its reflection in the Spanish cinema will be the subject of this article and the comparative profile of the Jewish German cinema.